Endothelial cell fitness dictates the source of regenerating liver vasculature - Singhal, Mahak; Liu, Xiaoting; Inverso, Donato; Jiang, Kai; Dai, Jianing; He, Hao; Bartels, Susanne; Li, Weiping; Abdul Pari, Ashik Ahmed; Gengenbacher, Nicolas; Besemfelder, Eva; Hui, Lijian; et al. (Journal of experimental medicine, 2018)
Graphical Abstract - Download figureOpen in new tabDownload powerpoint - - Neoangiogenesis plays a key role in diverse pathophysiological conditions, including liver regeneration. Yet, the source of new endothelial cells (ECs) remains elusive. By analyzing the regeneration of the liver vasculature in irradiation-based myeloablative and nonmyeloablative bone marrow transplantation mouse models, we discovered that neoangiogenesis in livers with intact endothelium was solely mediated by proliferation of resident ECs. However, following irradiation-induced EC damage, bone marrow-derived mononuclear cells were recruited and incorporated into the vasculature. Further experiments with direct bone marrow infusion or granulocyte colony-stimulating factor (G-CSF)-mediated progenitor cell mobilization, which resembles clinically relevant stem cell therapy, demonstrated that bone marrow-derived cells did not contribute to the regeneration of liver vasculature after two-thirds partial hepatectomy (PHx). Taken together, the data reconcile many of the discrepancies in the literature and highlight that the cellular source of regenerating endothelium depends on the fitness of the residual vasculature.